Not another 4th of July report: uncommon blast injuries to the hand. Issue 2 (22nd January 2008) - Frank, M; Schmucker, U; Hinz, P; Zach, A; Ekkernkamp, A; Matthes, G
Abstract : Objectives: Blast injuries to the hand are rare during peacetime and are mainly caused by fireworks. The injury patterns combine a variety of tissue destruction (laceration, dissemination, avulsion, blast, crush and burns). Emergency department staff play a key role in identifying the cause of injury, recognising the full extent of the lesion and referring patients for appropriate treatment. A review was undertaken to examine specificities in emergency department diagnosis and treatment of a separate subgroup of blast injuries. Methods: The diagnosis and treatment of patients admitted with work-related blast injuries of the hand were retrospectively reviewed. Demographic, clinical and diagnostic data were evaluated and treatment algorithms were analysed. Results: Treatment algorithms of 14 patients suffering blast injuries of the hand due to a vole captive bolt device were analysed. The non-homogeneous injury pattern showed complex multistructural lesions. Relatively innocent-looking superficial wounds mask extensive deep tissue damage, the full extent of which could only be recognised after rigorous surgical exploration. All patients but one were treated by immediate surgery, debridement of tissue necrosis and lavage. A delay before surgery resulted in phlegmonous infection in one case. Conclusion: Emergency staff must be aware of the potential dangers of this subgroup of blast injuries and the worsening effect of delay before surgery. Only knowledge of the underlying mechanism of the accident enables the emergency physician to understand the complexity and full extent of the injury pattern and to refer patients early for appropriate surgical management. Conservative treatment is inappropriate, dangerous and may become a focus of negligence claims.